Bionomia de mosquitos (Diptera: Culicidae) em áreas da Mata Atlântica no município de Itaguaí, estado do Rio de janeiro, Brasil: I. Frequência intra, peri e extradomiciliar Bionomics of mosquitoes (Diptera-Culicidae) in areas of the Atlantic Forest of Itaguaí municipality, Rio de Janeiro state, Brazil: I. intra, peri and extradomiciliary frequency - Anthony Érico Guimarães; Monique de Albuquerque Motta; Monique Arlé; Roberto Martins Machado; Luciene Dias Goncalves (Memorias do Instituto Oswaldo Cruz, 1989)
Along 24 consecutive months, from January 1984 to December 1986, mosquito captures were performed in a rural area of said municipality. Aiming to evaluate the comparative frequency of the mosquito species inside houses and in the immediate vicinity and far from houses, the captures were made in two types of domiciles - one permanently and the other only sporadically inhabited - as well as in surrounding woods. Variations in temperature, relative humidity and rainfall were locally recorded. A tendency for domiciliation became evident by the presence of Aedes scapularis in the human domiciles, mainly in those permantely inhabited. Culex quinquefasciatus showed to be adapted to live with humans also in rural areas, in which, in some instances, insecticides had to be used to keep in under control. Such observations, mainly in terms of Ae. scapularis, reinforce the possibility of those mosquitoes, under favourable conditions, becoming carries of arboviroses to humans in rural environments.